Renal Denervation Prevents Stroke and Brain Injury via Attenuation of Oxidative Stress in Hypertensive Rats. Issue 5 (14th October 2013) - Nakagawa, Takashi; Hasegawa, Yu; Uekawa, Ken; Ma, Mingjie; Katayama, Tetsuji; Sueta, Daisuke; Toyama, Kensuke; Kataoka, Keiichiro; Koibuchi, Nobutaka; Maeda, Masanobu; Kuratsu, Jun‐ichi; Kim‐Mitsuyama, Shokei
Abstract : Background: Although renal denervation (RD) is shown to reduce blood pressure significantly in patients with resistant hypertension, the benefit of RD in prevention of stroke is unknown. We hypothesized that RD can prevent the incidence of stroke and brain injury in hypertensive rats beyond blood pressure lowering. Methods and Results: High‐salt‐loaded, stroke‐prone, spontaneously hypertensive rats (SHRSP) were divided into 4 groups: (1) control; (2) sham operation; (3) bilateral RD; and (4) hydralazine administration to examine the effect of RD on stroke and brain injury of SHRSP. RD significantly reduced the onset of neurological deficit and death in SHRSP, and this protection against stroke by RD was associated with the increase in cerebral blood flow (CBF), the suppression of blood–brain barrier disruption, the limitation of white matter (WM) lesions, and the attenuation of macrophage infiltration and activated microglia. Furthermore, RD significantly attenuated brain oxidative stress, and NADPH oxidase subunits, P67 and Rac1 in SHRSP. On the other hand, hydralazine, with similar blood pressure lowering to RD, did not significantly suppress the onset of stroke and brain injury in SHRSP. Furthermore, RD prevented cardiac remodeling and vascular endothelial impairment in SHRSP. Conclusions: Our present work provided the first experimental evidence that RD can prevent hypertensive stroke and brain injury, beyond blood pressure lowering, thereby highlighting RD as a promising therapeutic strategy for stroke as well as hypertension.